The Influence of Digital Advertising Interactivity on Generation Z's Purchasing Intensity in the Fashion and Beauty Industry - Erick Lauren Ray; Franky Okto Bernando; Bayu Giri Prakosa (AIBPM Publisher, 2026)
The rapid growth of digital marketing has increased the importance of interactive advertising in influencing consumer behavior, particularly among Generation Z consumers in the fashion and beauty industry. This study aims to analyze the influence of digital advertising interactivity on purchase intensity, with attitude toward digital advertising serving as a mediating variable. This study employed a quantitative approach using data collected from 312 Generation Z respondents who actively use social media platforms and are frequently exposed to digital advertising. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital advertising interactivity has a positive and significant effect on attitude toward digital advertising (beta = 0.68; p 0.001) and purchase intensity (beta = 0.21; p = 0.002). In addition, attitude toward digital advertising significantly affects purchase intensity (beta = 0.54; p 0.001) and partially mediates the relationship between digital advertising interactivity and purchase intensity (beta = 0.37; p 0.001; VAF = 63.8%). The study concludes that interactive digital advertising strategies play an important role in enhancing consumer engagement and encouraging purchasing behavior among Generation Z consumers in the fashion and beauty industry.